1994
DOI: 10.1161/01.hyp.23.1_suppl.i256
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypertension and albuminuria in normotensive type I diabetic patients.

Abstract: An inherited predisposition to hypertension may increase susceptibility to nephropathy in type I diabetes. We evaluated the influence of a family history of essential hypertension on albuminuria in normotensive, normoalbuminuric type I diabetic patients. Forty-two diabetics (12.9±2.04 years) were divided into three groups according to tertiles of albumin excretion rate (group 1,1.27+0.35; group 2, 2.43±0.49; group 3, 6.37±3.43 jig/min; P<.001). Familial hypertension was considered to be present if the patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
1
0
2
Order By: Relevance
“…This is in good accordance with We evidenced an association between history of hypertension in relatives and diabetic nephropathy, as shown in some (8,9) but not all (43) previous reports. We found that mothers of nephropathic probands had higher SBP values than mothers of control subjects.…”
Section: Familial Datasupporting
confidence: 93%
“…This is in good accordance with We evidenced an association between history of hypertension in relatives and diabetic nephropathy, as shown in some (8,9) but not all (43) previous reports. We found that mothers of nephropathic probands had higher SBP values than mothers of control subjects.…”
Section: Familial Datasupporting
confidence: 93%
“…Patients with diabetes mellitus (DM) have risk of developing some complications such as diabetic nephropathy, diabetic retinopathy and cardiovascular disease. Especially, genetic factors, poor glycemic control and hypertension may play role in the diabetic complications coming up (Seaquist et al, 1989;Freire et al, 1994). Diabetic nephropathy is an important complication of diabetes mellitus of both type1 and type2 and is observed in up to 30% of patients, who suffer from non-insulin dependent diabetes mellitus (Nelson et al, 1991;Chowdhury et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos prospectivos de pacientes com DM2 (3,4,54,115,116) e de pacientes com DM1 (117,118), sugerem que mesmo níveis "normais altos" de EUA podem refletir o processo patológico que leva à ND. Um reforço para este achado é o de que jovens com DM1 no tercil superior de normoalbuminúria apresentam maior positividade de antecedentes familiares para hipertensão (119). Portanto, pacientes com risco de progressão para ND poderiam ser identificados antes de atingirem o valor adotado como critério a partir do qual é definida microalbuminúria (20µg/min).…”
Section: Neuropatia Autonômicaunclassified